The Implementation of the Empowerment Model of Women Farmer Groups “Minangkabau” in Managing Sustainable Food Security - Rinda Yanti; Hasan Ibrahim (MOZAIK HUMANIORA, 2021)
This research aims to explore the empowerment model of Minangkabau woman farmer groups was implemented to manage sustainable food security. "Minangkabau" farmer women groups in Koto Tuo Kenagarian were known not to be optimally empowered yet in managing food before. To pursue the purpose of this study, qualitative descriptive method was used together with system dynamics approach. The results of this research indicated that the implementation of empowerment model has successfully improved the potential and income of Minangkabau woman farmer groups. Their consumption patterns and nutritional knowledge have been increased from 62.50 percent before FGD to 74.60 percent after FGD. Moreover, their family health nutrition has been improved from 67.56 percent before FGD to 77.64 percent after FGD. Similarly, their food knowledge also has been elevated from 96.50 percent before FGD to 99.60 percent after FGD. And, 98 percent of "Minangkabau" farmer women groups even also has had more knowledge and skills related with diversify local food processing and food waste composting. In conclusion, the empowerment model for manging sustainable food security is very essential for Minangkabau woman farmer groups.